The Four Horsemen of New Atheism: A Select Bibliography. (2nd October 2019) - Finley, Wayne
Abstract: Between 2004 and 2007, four authors – Richard Dawkins, Daniel Dennett, Sam Harris, and Christopher Hitchens – published books critical of religion and promoting atheism. What set these works apart was that they were all published by major publishers and received critical acclaim. Three of the books would even go on to make the New York Times Best Seller list. Together, the four authors became know as the Four Horsemen of New Atheism. This article presents a brief overview of New Atheism and The Four Horsemen of New Atheism, author biographies, and reviews of the Four Horsemen's works from 2004–2007, which, collectively, outline the core ideas of the New Atheists.